Explanatory Analysis on Corporate Social Responsibility in Automotive Business and Brand Strategies - Martok, Yenni (Journal of Accounting and Management Innovation, 2021)
The purpose of this research is to understand the implementation of Corporate Social Responsibility (CSR) in the corporate growth and social development. It is obliged to promote social welfare to be put in the maximum economic benefits, including stakeholders in the companies. Some of the enterprises have increased the needs of CSR into the development of brand strategies and corporate governance in the responsibility of the mandatory environmental. It is also increased the needs of sustainability growth for the company. Automotive Business is characterized by numerous production processes and complex of diverse supply chain system. Automotive companies gives full play to the internal and cross industrial strengths. In this stage, CSR will become a way to contribute to society, laying the foundation for sustainable brand development and give more attention to social resources. It will lead to brand strategies and its relation with CSR in automotive business.Keyword: Corporate Social Responsibility, Automotive Business, Brand Strategies